Synthesis of N1 and N2 coumarin substituted 1, 2, 3-triazole isomers via click chemistry approach. Issue 5 (3rd March 2016) - Shamala, Devadas; Shivashankar, Kalegowda; Chandra,; Mahendra, Madegowda
ABSTRACT: The synthesis of N1 and N2 coumarin substituted 1, 2, 3-triazole isomers from terminal alkynes, sodium azide, and 4-bromomethylcoumarins in the presence of triethylamine as a base and CuI as a catalyst in good yield are reported. The molecular structure of compounds3g and5d are established by single-crystal analysis. GRAPHICAL ABSTRACT: